Mechanical Stress Analysis in High Power Press Pack IGBT - Xinling TANG; Zhongkang LIN; Xizi ZHANG; Shumin YAN; Bing SU; Liang WANG; Ronggang HAN; Hao SHI (Zhongguo dianli, 2020)
Mechanical stress is one of the key factors affecting the electrical characteristics, thermal characteristics and reliability of high-voltage high-power press-pack IGBT devices. First of all, in this paper, from the perspective of chip and package structure design, the research status and key design techniques of the uniformity of the mechanical pressure distribution of single-chip and parallel multi-chip are introduced. Secondly, from the perspective of packaging technology, the influence of compliant contact, rigid contact and different soldering forms on the mechanical stress distribution of the chips are compared. Finally, combined with the characteristics of the press-pack structure, and based on a new type of edge termination structure, a new packaging technology solution is proposed, which can effectively improve the uniformity of the pressure of single chips and parallel chips, so as to provide a reference for the design of high-voltage high-power press-pack IGBT devices.